2011
DOI: 10.1016/j.jbmt.2009.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The immediate effects of traditional Thai massage on heart rate variability and stress-related parameters in patients with back pain associated with myofascial trigger points

Abstract: The purpose of this study was to investigate the immediate effects of traditional Thai massage (TTM) on stress-related parameters including heart rate variability (HRV), anxiety, muscle tension, pain intensity, pressure pain threshold, and body flexibility in patients with back pain associated with myofascial trigger points. Thirty-six patients were randomly allocated to receive a 30-min session of either TTM or control (rest on bed) for one session. Results indicated that TTM was associated with significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 24 publications
9
88
0
4
Order By: Relevance
“…In relation to the study on massage, it was observed that it promotes relaxation, and reduces stress and anxiety (27) . The study that used palm therapy was based on the theory that the palm of the hand represents the entire body in miniature and that certain points correspond to specific areas of the brain, both motor and sensory.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the study on massage, it was observed that it promotes relaxation, and reduces stress and anxiety (27) . The study that used palm therapy was based on the theory that the palm of the hand represents the entire body in miniature and that certain points correspond to specific areas of the brain, both motor and sensory.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of heart rate after the massage may also be related to the anxiolytic and Para sympathomimetic effects of massage (Buttagat et al, 2011;Lindgren et al, 2010). This is supported by Diego and Field who showed that the massage applied at medium pressure for 15minutes caused increase in the highfrequency component of HR variability which reflected an increase in vagal activities.…”
Section: Discussionmentioning
confidence: 99%
“…Contact information for these therapists was obtained through the Iowa Department of Public Health website. (25) Massage therapists in Iowa were chosen for two primary reasons. First, previous studies have not explored massage therapy practice in the Midwest.…”
Section: Methods Participantsmentioning
confidence: 99%